Oxidative Damage in Lymphocytes of Copper Smelter Workers Correlated to Higher Levels of Excreted Arsenic. (28th December 2010) - Escobar, Jorge; Varela-Nallar, Lorena; Coddou, Claudio; Nelson, Pablo; Maisey, Kevin; Valdés, Daniel; Aspee, Alexis; Espinosa, Victoria; Rozas, Carlos; Montoya, Margarita; Mandiola, Cristian; Rodríguez, Felipe E.; et al.
Abstract : Arsenic has been associated with multiple harmful effects at the cellular level. Indirectly these defects could be related to impairment of the integrity of the immune system, in particular in lymphoid population. To characterize the effect of Arsenic on redox status on this population, copper smelter workers and arsenic unexposed donors were recruited for this study. We analyzed urine samples and lymphocyte enriched fractions from donors to determinate arsenic levels and lymphocyte proliferation. Moreover, we studied the presence of oxidative markers MDA, vitamin E and SOD activity in donor plasma. Here we demonstrated that in human beings exposed to high arsenic concentrations, lymphocyte MDA and arsenic urinary levels showed a positive correlation with SOD activity, and a negative correlation with vitamin E serum levels. Strikingly, lymphocytes from the arsenic exposed population respond to a polyclonal stimulator, phytohemaglutinin, with higher rates of thymidine incorporation than lymphocytes of a control population. As well, similar in vitro responses to arsenic were observed using a T cell line. Our results suggest that chronic human exposure to arsenic induces oxidative damage in lymphocytes and could be considered more relevant than evaluation of T cell surveillance.